Productivity and Tax Evasion - Era Dabla-Norris; Mark Gradstein; Fedor Miryugin; Florian Misch (Center for Economic Studies and ifo Institute (CESifo), 2019)
The extent of tax compliance has important implications for revenue yield, efficiency and the fairness of any tax system. Tax evasion undermines revenue collection, distorts competition, and undermines a country's development prospects. In this paper, we investigate whether higher productivity causally leads to lower tax evasion. We first present stylized facts consistent with this view and develop a model that illustrates one potential transmission channel. Second, we test the model predictions at the firm level using the self-reported share of declared income as proxy for tax evasion for a large sample of emerging and developing economies. Our results suggests that productivity improvements by firms can lead to lower tax evasion.
Keywords: D20; H26; O47; 330; economic development; firm productivity; tax evasion